Advanced Potential Field Analysis Applied to Mise‐à‐la‐Masse Surveys for Leakage Detection. Issue 11 (12th November 2022) - Mary, Benjamin; Peruzzo, Luca; Wu, Yuxin; Cassiani, Giorgio
Abstract: Traditionally interpretation of Mise‐à‐la‐masse (MALM) is limited to the visualization of equipotential contours in order to infer qualitatively the extent of the anomaly. MALM inversion algorithms rely on having a good knowledge of the electrical resistivity distribution in the subsoil. Conversely, potential imaging methods have shown their strength for several applications to quickly estimate the depth of sources even in highly heterogeneous media. In the case of the MALM method, the physics may be described by Poisson's equation. As the conductivity term is modulating the flux of current, MALM is generally referred to as a pseudo‐potential method. In this work, we have tested, for the first time, the application of the potential field theory to MALM in order to identify the current source depth. Synthetic modeling shows that the proposed algorithm is effective and efficient, using surface voltage measurements for different resistivity contrasts, anomaly depths and noise levels. We then applied the method to the real field case of a landfill leakage and showed how very different source depth estimates result from an intact or a damaged landfill liner. Plain Language Summary: The so‐called Mise‐à‐la‐Masse (MALM) technique is a well‐known active geoelectrical prospection method aimed at imaging (qualitatively) electrically conductive (often ore) bodies in the subsurface. The current is injected in the core of the body to prospect, and the high electrical conductivity of the body channels the current making it detectable from the anomalies of electrical potential measured, for example, at the ground surface. Verification of landfill liner integrity is one of the most recent applications of MALM, exploiting the electrical and hydraulic separation, often made with a plastic liner, between the conductive waste inside and the soil outside. Holes in the liner may be imaged inducing a passage of direct current (DC) between the inner and the outer part of the landfill, provided that the location of such holes be identified using an efficient MALM inversion. For this purpose, we adapted an algorithm used for voltage inversion to MALM: the approach has proven effective using synthetic modeling and was successfully applied to real field data from an industrial landfill. Key Points: We have developed the potential field imaging theory to estimate the depth of current sources in Mise‐à‐la‐masse surveys Synthetic and field applications of a landfill leakage is demonstrated An Open‐source code for inversion of voltage using potential field imaging theory is provided